Proceedings of the Forty-Fourth Annual ACM Symposium on Theory of Computing 2012
DOI: 10.1145/2213977.2214036
|View full text |Cite
|
Sign up to set email alerts
|

Affine projections of polynomials

Abstract: An m-variate polynomial f is said to be an affine projection of some n-variate polynomial g if there exists an n × m matrix A and an n-dimensional vector b such that f (x) = g(Ax + b). In other words, if f can be obtained by replacing each variable of g by an affine combination of the variables occurring in f , then it is said to be an affine projection of g. Given f and g can we determine whether f is an affine projection of g? Some well known problems (such as VP versus VNP and matrix multiplication for exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 43 publications
0
60
0
Order By: Relevance
“…Kayal [Kay12a] showed that ∂ =1 f ≤1 yields a lie algebra that can help efficiently determine if f is equivalent (via an affine change of variables) to the permanent (or determinant). For = ∞, note that ∂ =k f ≤ is precisely the ideal generated by the k-th order derivatives of f .…”
Section: Basic Idea and Outlinementioning
confidence: 99%
“…Kayal [Kay12a] showed that ∂ =1 f ≤1 yields a lie algebra that can help efficiently determine if f is equivalent (via an affine change of variables) to the permanent (or determinant). For = ∞, note that ∂ =k f ≤ is precisely the ideal generated by the k-th order derivatives of f .…”
Section: Basic Idea and Outlinementioning
confidence: 99%
“…The algorithmic study of Model 1.2 is usually attributed to Sylvester. We refer to [15] for the historical background and to section 1.3 of that book for a description of the algorithm (see also Kleppe [17] and Proposition 46 of Kayal [18]). Most of the subsequent work was devoted to the multivariate generalization 1 of Model 1.2, with much of the 20th century work focused on the determination of the Waring rank of generic polynomials [1,7,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, he provides randomized algorithms for the affine-equivalence problem when one of the polynomials is the Permanent or the Determinant and the affine transformations x → Ax + b are of a special form (in the case of Determinant and Permanent, the matrix A must be invertible). Kayal provides randomized algorithms for some other classes of homogeneous polynomials, and for more details we refer the reader to the paper [Kay12]. Our work is different from Kayal's work since in our setting we are only interested in shift-equivalences, and in this feature we are less general than Kayal's work, but we also consider larger classes of polynomials, in which case we are more general than Kayal's work.…”
Section: Related Workmentioning
confidence: 99%
“…The study of equivalences of general polynomials under affine transformations, which we refer to as affine-equivalence, was started by Kayal in [Kay12] (note that this generalizes the problem studied in [GK93]). We say that f and g are affine-equivalent if there exists a matrix A and a shift b such that f (x) = g(Ax + b).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation